CYP2A6 and CYP2E1 polymorphisms in a Brazilian population living in Rio de Janeiro - Rossini,A. (2006)
Cytochrome P450 (CYP) is a superfamily of enzymes involved in the metabolism of endogenous compounds and xenobiotics. CYP2A6 catalyzes the oxidation of nicotine and the activation of carcinogens such as aflatoxin B1 and nitrosamines. CYP2E1 metabolizes ethanol and other low-molecular weight compounds and can also activate nitrosamines. The CYP2A6 and CYP2E1 genes are polymorphic, altering their catalytic activities and susceptibility to cancer and other diseases. A number of polymorphisms described are ethnic-dependent. In the present study, we determined the genotype and allele frequencies of the main CYP2A6 and CYP2E1 polymorphisms in a group of 289 volunteers recruited at the Central Laboratory of Hospital Universitário Pedro Ernesto. They had been residing in the city of Rio de Janeiro for at least 6 months and were divided into two groups according to skin color (white and non-white). The alleles were determined by allele specific PCR (CYP2A6) or by PCR-RFLP (CYP2E1). The frequencies of the CYP2A6*1B and CYP2A6*2 alleles were 0.29 and 0.02 for white individuals and 0.24 and 0.01 for non-white individuals, respectively. The CYP2A6*5 allele was not found in the population studied. Regarding the CYP2E1*5B allele, we found a frequency of 0.07 in white individuals, which was statistically different (P < 0.05) from that present in non-white individuals (0.03). CYP2E1*6 allele frequency was the same (0.08) in both groups. The frequencies of CYP2A6*1B, CYP2A6*2 and CYP2E1*6 alleles in Brazilians are similar to those found in Caucasians and African-Americans, but the frequency of the CYP2E1*5B allele is higher in Brazilians.